The prevalence of suboptimal health status among Chinese secondary school students and its relationship with family health: the mediating role of perceived stress and problematic internet use - Benli Xue; Xiao Zheng; Lingli Yang; Shujuan Xiao; Jingwen Chen; Xinyi Zhang; Xinru Li; Yiming Chen; Yanming Liao; Mengjie Zhang; Ting Zheng; Yibo Wu; et al. (BMC Public Health)
Abstract Background The health status of secondary school students has received widespread attention, and family plays an extremely important role in protecting and promoting their health. However, the relationship between family health and suboptimal health status (SHS) among secondary school students and its underlying mechanisms are unclear. This study aims to understand the prevalence of SHS among Chinese secondary school students and analyze the relationship between family health and SHS, and examine the mediating roles of perceived stress and problematic internet use. Methods The 2,094 secondary school students (52.6% boys, 47.4% girls, M age ± SD = 15.74 ± 1.78) of this study came from “2022 Psychology and Behavior Investigation of Chinese Residents, PBICR”. The chi-square test and t-test were used to analyze the prevalence of SHS in secondary school students with different characteristics. The SPSS PROCESS macro software was used to explore the relationship between family health and SHS and the mediating effects of perceived stress and problematic internet use. Results The prevalence of SHS among Chinese secondary school students was 40.7%, and older students, girls, non-only child, high school students, smokers, drinkers, and students living in the Northeast region of China had higher prevalence. Family health, SHS, perceived stress, and problematic internet use were significantly related (P < 0.001). Family health had a negative effect on SHS (β = -0.127, 95% CI: -0.173 to -0.080). At the same time, perceived stress mediated the relationship between family health and SHS (chain mediation model 1: β = -0.109, 95% CI: -0.133 to -0.087; chain mediation model 2: β = -0.098, 95% CI: -0.120 to -0.078) and problematic internet use also mediated their relationship (chain mediation model 1: β = -0.034, 95% CI: -0.056 to -0.014; chain mediation model 2: β = -0.077, 95% CI: -0.099 to -0.055). The chain mediating effect of perceived stress and problematic internet use was also found in this study and the chain path from family health to perceived stress to problematic internet use to SHS was superior (β = -0.043, 95% CI: -0.054 to -0.033). Conclusions Many secondary school students are experiencing SHS. Improving family health, such as strengthening parent–child communication and fostering positive parenting practice, is critical to improving their health. Helping secondary school students relieve perceived stress and reduce their problematic internet use is key to implementing family-oriented health interventions.